DESIGN AND CHARACTERIZATION OF NANOSPRAY WITH SELF-NANOEMULSIFYING DRUG DELIVERY SYSTEM USING SINERGISTIC COMBINATION OF MELASTOMA MALABATHRICUM L. FRACTION AND GENTAMICIN - PRATIWI, LIZA; SARI, RAFIKA; APRIDAMAYANTI, PRATIWI (International Journal of Applied Pharmaceutics, 2021)
Objective: This study aimed to design a formula using Design-Expert software to obtain optimal Self-Nanoemulsifying Drug Delivery System (SNEDDS) formulas and to analyze nanospray characteristics of optimal SNEDDS. Methods: The study began with preparing ethanol extract from Melastoma malabathricum. The extract was then fractionated using ethyl acetate. The formulation design stage began with a solubility test of Melastoma malabathricum fraction and gentamicin (MFG) in various surfactants, co-surfactants and oils. Furthermore, the 14 formula of SNEDDS with various compositions of the selected surfactants, co-surfactants and oils were formulated and evaluated with pH response and emulsification time. Analysis was carried out using Design-Expert software with the simplex lattice design method in order to obtain the optimal formula profile. The pH, emulsification time, particle size, and zeta potential of the nanospray from SNEDDS optimal formulas were physically characterized. Stability of SNEDDS and the nanospray was then tested with freeze-thaw cycling and in vitro diffusion studies with Franz diffusion. Results: Based on the study, the ratios of optimal formula SNEDDS composition of Tween 80, propylene glycol, and soybean oil were 2.69: 2.64: 1.67 parts. Nanospray with SNEDDS technology had characteristics of pH 5.61±0.16, emulsification time 7.68±0.18, particle size 270.7 nm, and zeta potential-37.20 mV, and it was stable. Conclusion: Nanospray can be formulated from optimal SNEDDS using Design-Expert software. Nanospray with SNEDDS technology has physical characteristics and is stable. In vitro diffusion studies revealed that the release of Melastoma malabathricum from nanospray was faster than that without preparation.